“Pitch the king”: Ben Fountain’s games - Françoise Palleau-Papin (Association Française d'Etudes Américaines, 2013)
In his stories and his novel, Ben Fountain uses games as an epistemological tool. Games allow him to subvert the cultural codes, his satire becoming a political critique of the nation and of US foreign policy, and to operate a fusion of the characters’ voices, as he looks for a collective or transpersonal expression. He ultimately plays with his readers, inviting them to be active recipients and discoverers.